Character association and Path analysis of some Quantitative and Qualitative traits among interspecific crosses of Gossypium arboreum and Gossypium herbaceum - S.Saravanan and K. Koodalingam (Electronic Journal of Plant Breeding, 2011)
Studies on correlation indicated that intensive selection on the positive side for plant height, sympodia per plant, seed index, lintindex, 2.5 per cent span length and bolls per plant since these characters showed positive correlation with seed cotton yield andalso positive correlation among themselves. Days to flower initiation, micronaire value and elongation per cent showed negativecorrelation with seed cotton yield and hence a compromise towards selection is required in this case. Path coefficient analysisfurther revealed that bolls per plant played a major role in determining the seed cotton yield.